(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Engineering education in India has seen a major change in the last few years. Due to the generous increase in interest towards high quality education, information and communication technology has been accepted to enhance the education endeavor. Academic libraries in engineering institutions are well-known information organizations and play an essential function in meeting the information needs of users. The present chapter focuses on the analysis of data and interpretation of results related to research studies in engineering college libraries in Chhattisgarh from primary data collected from engineering college libraries affiliated to Government Engineering Colleges (GEC) of Chhattisgarh state. The results obtained based on the opinions of the responses received are presented in detail in this chapter. The results are clearly presented institution wise as percentage of respondents and total respondents as well as designation of the respondent. The data obtained from the detailed questionnaire of the study was analyzed statistically and the results are presented in detail with discussion in this chapter to meet the objectives of the study.